CBN @ 50 - Central Bank of Nigeria; Central Bannk of Nigeria (Abuja, Nigeria : Central Bank of Nigeria, 2009)
Provides a pictorial insight into how the mandate of the Bank, right from its inception has been implemented and an illustration of the various landmarks that have come to characterize what the Central Bank of Nigeria stands for today.
"CBN Golden Jubilee (1959 - 2009)". ---Cover
oif 04/12/14
Loan
Keywords: Banks and banking, Central; Money